GAYA BAHASA PERBANDINGAN DALAM KUMPULAN CERPEN SAGRA KARYA OKA RUSMINI - Harmila Sari Umar; La Ode Syukur; saidiman (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study aims to describe the types of comparative language styles in the short story collection Sagra by Oka Rusmini. The type of research used in this study is library research. The method used in this study is descriptive analysis. The data in this study is the short story collection Sagra by Oka Rusmini published by PT Gramedia Widiasarana Indonesia in Jakarta, consisting of 204 pages and 13 short story titles. The three selected short stories are (1) Esensi Nobelia, (2) Sepotong Kaki, (3) Sagra. The data collection technique uses the reading and note-taking technique. The data analysis technique used is the objective approach. The results of this study indicate that (1) the short story Esensi Nobelia contains 4 types of comparative language styles, namely simile, metaphor, personification, and anticipation (2) the short story Sepotong Kaki contains 3 types of measurement language styles, namely simile, metaphor, and personification (3) the short story Sagra contains 4 types of comparative language styles, namely simile, metaphor, personification, and pleonasm.